Specific Issues of Equivalent Longitudinal Resistances Calculation for Three Windings Transformers - Golovanov N.; Porumb R.; Toader C.; Bulac C.; Triştiu I.; Seritsan G. (Problems of the Regional Energetics, 2015)
ccomplishing the aspirations of electrical power engineering consists, nowadays, in accurately determining the operating modes. Knowing the parameters of network elements is imperative for accurate solving the power flow regimes. This paper addresses unitarily the calculation of longitudinal resistance of three windings transformers and autotransformers, considering its rated parameters, and discussing the validity of relations demonstrated in detail.